Fintech P2P Lending in Increasing People's Purchasing Power in South Sulawesi Province - Karim, Abdul; Ruslan, Muhlis; Chahyono, Chahyono; Yunus, Muh. Kafrawi; Ahmad, Amrullah (Bina Nusantara University, 2024)
The research aimed to assess the extent to which fintech P2P lending contributes to the generation of purchasing power in South Sulawesi Province. Data were collected from websites associated with fintech P2P lending and analyzed using software designed for indexing, searching, and handling non-numerical and unstructured data. The findings indicate that the availability of online loans positively impacts economic growth in South Sulawesi. During the final seven months of 2023, the average monthly distribution of peer-to-peer (P2P) lending funds reached IDR 19.04 trillion. The total distribution within the industry amounted to IDR 20.38 trillion, with IDR 7.26 trillion (35.65 percent) allocated to the productive sector, including micro, small, and medium-sized enterprises (MSMEs). This research contributes to the field by observing a 30.17 percent increase in credit in South Sulawesi Province. In February 2024, individual credit distribution in South Sulawesi reached IDR 1.29 trillion, based on 355,948 credit transactions. Fintech P2P lending helps improve financial literacy and inclusion in the South Sulawesi region by providing an easy-to-use digital platform to reach people in remote areas and support more equitable economic development. The contribution of fintech P2P lending plays an important role in increasing people's purchasing power while strengthening the foundation of the local economy in South Sulawesi.